PENGARUH KOMBINASI PUPUK FOSFAT DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (GLYCINE MAX L) VARIETAS ANJASMORO - Rifai, Akhmad Anang; Tadjudin, Endang; Efendi, Ali (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2023)
This experiment aims to determine the effect of the combination of phosphate fertilizer and plant spacing on the growth and yield of soybean (Glycine smax L.) Anjasmoro variety. The experiment was carried out in Mekarjaya Village, Gantar District, Indramayu Regency - West Java. The time of the research was carried out from August to October 2021. The location is located at an altitude of ± 50 meters above sea level (masl), the soil type is the association of Latosol and Regosol, including type D (moderate) rain. The experimental method used is the experimental method with a factorial randomized block design (RAK), treatment consists of 2 factors repeated three times. The first factor is the spacing which consists of three levels, namely 40 cm x 25 cm, 40 cm x 30 cm, and 40 cm x 40 cm. While the second factor is the dose of phosphate fertilizer which consists of three levels, namely 100 kg/ha, 150 kg/ha, and 200 kg/ha. The main observation data were processed using linear model statistical tests, analysis of variance, and Scott-Knot cluster further test analysis. To determine the correlation between the treatment with the components of growth and yield of soybeans, the correlation used is the Product Moment correlation coefficient. The experimental results showed: (1) The combination of phosphate fertilizer and plant spacing affected the number of leaves at 14 DAP, the number of branches at 28 and 35 DAP, leaf area index at 14, 28, and 35 DAP (2) Dry seed weight per plot The highest yield was produced by the combination of treatment F, with a spacing of 40 cm x 30 cm and a phosphate dose of 200 kg/ha with a dry harvest weight of 0.711 kg per plot (equivalent to 1.8 tons/ha), and (3) There was a significant correlation between height plants aged 28 DAP and 35 DAP and the number of leaves at 28 DAP with dry seed weight per plot.